OWNER DEMOGRAPHICS INFLUENCE KNOWLEDGE OF SELLING PRICE DETERMINATION - Halimatusadiah, Elly; Rosdiana, Yuni; Mardini, Riyang; Pramono, Irena Paramita (Kajian Akuntansi, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy, especially in West Java Province. However, the main challenge faced by MSMEs is a lack of knowledge about accounting and cost management, including calculating the Cost of Goods Production and overhead costs, which influence the determination of product selling prices. This research aims to analyze the influence of MSME Owner Demographics on knowledge of selling price determination. The research methodology uses a verification method with a quantitative approach. The research population was all MSME owners in West Java Province, with samples taken using a purposive sampling technique. Primary data was obtained through a closed questionnaire with a Likert scale, which included questions about owner demographics, knowledge of COGS, overhead costs, and determining product selling prices. Data analysis was carried out using linear regression to test the influence of the independent variable on the dependent variable. Convergent and discriminant validity as well as construct reliability have been tested and show that all indicators and constructs in this model are valid and reliable. The results of the research show that Owner Demographics of MSMEs influence knowledge of selling price determination. Keywords          : COGS, Determining Selling Prices, MSMEs, Overhead Costs, Owner Demographics.